2021
DOI: 10.1021/acs.macromol.1c01692
|View full text |Cite
|
Sign up to set email alerts
|

Uniting Group-Transfer and Ring-Opening Polymerization─Block Copolymers from Functional Michael-Type Monomers and Lactones

Abstract: Herein, the consecutive group-transfer polymerization (GTP) of the Michael-type monomer 2-vinylpyridine (2VP) and ring-opening polymerization (ROP) of ε-caprolactone (CL) or (−)-menthide (M) using a monometallic and a bimetallic 2-methoxaminethylamino-bis­(phenolate) yttrium catalyst for the synthesis of AB- and BAB-type block copolymers (P2VP-b-PCL and P2VP-b-PM) are reported. Using the more demanding (−)-menthide, further insights into the catalytic nature of this combinatorial polymerization approach were g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…S38 †). 42,43 Nevertheless, all catalysts were capable of polymerizing εCarL under the tested conditions, yielding defined P(εCarL) for the first time (Fig. 1, left).…”
Section: Resultsmentioning
confidence: 93%
“…S38 †). 42,43 Nevertheless, all catalysts were capable of polymerizing εCarL under the tested conditions, yielding defined P(εCarL) for the first time (Fig. 1, left).…”
Section: Resultsmentioning
confidence: 93%
“…[147] After symcollidine and TMPy were reported to undergo 𝜎-bond metathesis with [ONOO] tBu Y(CH 2 TMS)(THF) to enable AB-and BAB-block copolymers either via group-transfer or via ring-opening polymerization, another attempt was made to produce block copolymers from Michael-type monomers and lactones. [160] Another modification implemented was the transition from the fourmembered lactone BBL to larger-sized lactones, i.e., the sevenmembered ring lactones 𝜖CL and (−)-menthide. It was shown that the active chain end of P2VP itself can successfully initiate the polymerization of these seven-membered lactones leading to AB or BAB polymers (Scheme 13).…”
Section: Copolymer Architecturesmentioning
confidence: 99%
“…Moreover, the presence of two functionalizable motifs per monomer unit allows doubling of the attached molecules per repeating unit, resulting in a higher loading capacity. Our group has successfully achieved well-defined, high molecular-weight polyvinyl phosphonates via living rare-earth metal-mediated group transfer polymerization (REM-GTP). This method enables excellent control over the polymer microstructure in terms of copolymer composition and the creation of block structures with various functional monomers while maintaining a narrow polydispersity. Besides, various modification options are available, including end-group functionalization with different initiators functionalized with azides, allyl groups, or other protected reactive groups. , Moreover, modifying polymers through postpolymerization functionalization or incorporating diverse functional monomer units is feasible. , Furthermore, amphiphilic block copolymers containing polyvinyl phosphonates have been studied for their micellar formation, loading and release behavior, and modification options. ,, Postpolymerization functionalization also allows the attachment of different biologically active substrates to the polymer.…”
Section: Introductionmentioning
confidence: 99%